Integration of holistic education concepts in higher education to building mental health-friendly campuses: Case study from Indonesia - Minsih, Minsih; Lawton, Megan; Sudarmilah, Endah; Rahmawati, Fitri Puji; Mujahid, Imam; Sari, Anggun Yunita (Psikohumaniora: Jurnal Penelitian Psikologi, 2024)
In response to the rising mental health issues among students, higher education institutions are called to adopt more comprehensive strategies for supporting mental well-being. While there is significant research on mental health in higher education, studies focusing on integrating holistic education to promote mental health remain limited. This research aims to explore how holistic education can transform higher education and create a mental health-friendly campus environment. A qualitative approach was used, including in-depth interviews, document analysis, and observations of holistic education practices. The study involved 42 students, 14 lecturers, 5 administrators, and 2 counseling staff members. Data were validated through triangulation, ensuring reliability. The findings suggest that creating a mental health-friendly campus begins with open mental health policies. Integrating holistic education into curricula and support systems is crucial for improving academic performance and social engagement. This approach encourages active student participation, making learning more relevant to real life. Additionally, fostering a campus culture focused on mental health, involving students in activities, and building community is essential. The study also stresses the importance of raising awareness of mental health and the role of lecturers in supporting students' well-being.